Students’ perception towards career opportunities in hotel and tourism industry / Nur Aqilah Muhamad Zahurin & Nur Fatihah Natasya Abdullah - Muhamad Zahurin, Nur Aqilah; Abdullah, Nur Fatihah Natasya (Faculty of Hotel and Tourism, Universiti Teknologi MARA,Terengganu, 2018)
Hospitality is the one of the fastest growing industries in the world1: (Peoplelst, 2011). Moreover, hospitality and tourism industry have become a second contributor to national economic after oil and gas industry. The purpose of this study is to investigate the perception of the students towards hotel and tourism management program in career opportunities. This is because we would like to research about university students regarding them studying in the hospitality program and their career opportunities. By using secondary data that was develop to identify the perception towards the hospitality education and to analyses if they are interested on going further in this road. This research will provide a valuable information regarding of student perception towards hotel and tourism management program in career opportunities. This research hopefully brings clearer vision to those seeks more information in this study.